Respon Remaja Tentang Kasus Cyberbullying Sulli Dan Goo Hara - Dwi Putri Robiatul Adawiyah; Muhammad Munir (Jurnal Komunikasi, 2021)
Abstract. Cyberbullying is the act of hurting, embarrassing, or distressing people because all the disgrace is publicized on social media. The victim becomes depressed and commits dangerous things such as suicide. This study aims to explain adolescent responses about Sulli and Goo Hara's cyberbullying that cause death. The author applied descriptive qualitative methods. The results revealed the lack of netizen knowledge and consequences on Sulli and Goo Hara's mental health made them not careful in commenting on social media. Therefore, it is important for netizens to be careful about everything that will be posted on social media in order not to get meanly impact to others.Keywords: Response, Youth, Cyberbullying, fans